Measurement of HΛ3 production in Pb–Pb collisions at sNN=5.02 TeV - Acharya, S.; Basu, S. ; 0000-0003-0687-8124; Christiansen, P.; Hansen, J. ; 0009-0008-4642-7807; Iversen, K.E. ; 0000-0001-6533-4085; Matonoha, O.; Nepeivoda, R. ; 0000-0001-6412-7981; Ohlson, A.; Silvermyr, D. ; 0000-0002-0526-5791; Staa, J.; Zurlo, N. (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
The first measurement of HΛ3 and H‾Λ‾3 differential production with respect to transverse momentum and centrality in Pb–Pb collisions at sNN=5.02 TeV is presented. The HΛ3 has been reconstructed via its two-charged-body decay channel, i.e., HΛ3→3He+π−. A Blast-Wave model fit of the pT-differential spectra of all nuclear species measured by the ALICE collaboration suggests that the HΛ3 kinetic freeze-out surface is consistent with that of other nuclei. The ratio between the integrated yields of HΛ3 and He3 is compared to predictions from the statistical hadronisation model and the coalescence model, with the latter being favoured by the presented measurements. © 2024 CERN for the benefit of the ALICE Collaboration